Modelado matemático de la posición del centro de masa de un robot de tracción diferencial. Un Enfoque desde la Mecánica Lagrangiana (2023)
The target of this paper is to develop and validate a mathematical model to determine the center of mass’ position and orientation of a mobile robot (NXT LEGO Kit 2.0). The model takes into account input voltage applied to wheel’s servomotors and is formulated using dynamic and kinematics of the robot with a Lagrangian mechanics approach. Experimental results are obtained using the so-called Tracker software. Subsequently, data is processed using a t-student test, comparing experimental data with simulation results, which are obtained executing the model in Matlab-Simulink. As a result, the mathematical model accurately describes the behavior of the robot’s center of mass. © Centro de Informacion Tecnologica. All rights reserved.